INVESTIGATING THE USE OF PORTFOLIO ASSESSMENT IN ENGLISH CLASSROOMS - Safitri, Rahmi (2014)
This study was conducted to investigate the use of portfolio in the classroom in one private senior high school in Bandung, and to identify the obstacles faced by the teacher and students in implementing the portfolio assessment. This study employed a case study research design. The data were obtained through observation in which the researcher acted as a non- participant observer, a set of open and close questionnaire and semi-structured interviews. The data were analyzed qualitatively and quantitatively. Quantitative data were used to analyze the result of questionnaire through percentage in order to find out students' respond in implementing portfolio. Qualitative data were used to describe the result of classroom observations and interviews to answer question related with the implementation of portfolio assessment in the classroom and to find out the obstacles faced by the teacher and students. The result from observation revealed that teacher had implemented some stages in implementing portfolio. The stages were deciding a purpose or theme, introducing and showing the example of portfolio, specifying portfolio content, developing and appropriate scoring system, assessing and giving feedback to students. Data from observation also showed that teacher had implemented self-assessment which was one of important aspects in portfolio and this was supported by data from interview that said self-assessment was used to gain students' understanding of their own strengths and weaknesses. Moreover, data from questionnaire indicated that students had positive responses through the implementation of portfolio and it was supported by data from interview which showed that creating portfolio made them realize their strengths and weaknesses in learning English and made their skill specifically in writing and speaking increased. However, there were some limitations in this study, the limitations were seen from the obstacles faced by both students and teacher. Students' obstacles happened when they had to finish the self-assessment, some important documents lost thus they couldn't create their portfolio as their expectation, and cost problem which they had to spend some expenses for making their portfolio looked better than others and to make it as complete as possible. Meanwhile, the obstacles faced by the teacher were the limitation of time in checking and giving feedback to students' tasks and the missing stages indicated that teacher didn't fully understand about the implementation of portfolio due to his knowledge of portfolio has not been adequate. Therefore, teacher should read some sources related with portfolio and when government hold a training teacher doesn't come with an empty head. Key words: Portfolio Assessment, Implementation Penelitian ini ditujukan untuk menginvestigasi penggunaan portfolio di dalam kelas di salah satu sekolah menengah atas di Bandung, dan untuk mengidentifikasi kesulitan yang dihadapi oleh guru dan siswa dalam menerapkan penilaian portfolio. Penelitian ini menggunakan metode penelitian studi kasus. Data didapatkan melalui observasi, kuesioner dan wawancara. Data dianalisis secara kualitatif dan kuantitatif. Kuantitatif data digunakan untuk menganalisis data kuesioner melalui persentase yang bertujuan untuk mengetahui respon siswa dalam penerapan portfolio. Kualitatif data digunakan untuk mendeskripsikan hasil dari observasi kelas dan hasil wawancara guna menjawab pertanyaan yang berkaitan dengan penerapan portfolio didalam kelas dan untuk menemukan hambatan yang dihadapi oleh guru dan siswa. Hasil dari observasi menunjukkan bahwa guru telah melaksanakan beberapa tahap dalam proses pelaksanaan portfolio. Tahap-tahap tersebut ialah menentukan tujuan atau tema, memperkenalkan dan menunjukkan contoh portfolio, menentukan isi portfolio, mengembangkan sistem penilaian yang sesuai, memberikan penilaian dan masukan kepada siswa. Data dari observasi menunjukkan bahwa guru melaksanakan self-assessment (penilaian diri) yang merupakan salah satu aspek penting dalam portfolio dan hal ini didukung oleh data dari wawancara yang menyatakan bahwa self-assessment digunakan untuk mendapatkan pemahaman siswa atas kekurangan dan kelebihan diri mereka sendiri. Data dari kuesioner mengindikasikan bahwa siswa memiliki respon yang positif terhadap penerapan portfolio. Sementara itu, masalah yang dihadapi oleh siswa terjadi saat mereka harus menyelesaikan self-assessment, hilangnya beberapa dokumen yang harus dikumpulkan dan biaya yang harus dikeluarkan untuk membuat portfolio secara baik. Dilain pihak, masalah yang dihadapi guru ialah terbatasnya waktu untuk memeriksa tugas siswa satu per satu dan hilangnya beberapa tahap dalam proses penerapan portfolio mengindikasikan bahwa guru tidak memahami sepenuhnya bagaimana menerapkan portfolio didalam kelas. Hal ini dikarenakan kurangnya pengetahuan mereka atas portfolio. Oleh karena itu, guru seharusnya membaca beberapa sumber yang berkaitan dengan portfolio sehingga saat pemerintah mengadakan pelatihan, guru tidak datang dengan kepala kosong. Kata kunci: Penilaian portfolio, Penerapan